Pengaruh Variasi Normalitas NaOH pada Aktivasi Basa-Fisik Zeolit Pelet Perekat terhadap Prestasi Sepeda Motor Bensin 4-Langkah - Herry Wardono (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2014)
Natural zeolite is an alternative adsorbent. It needs firstly to be activated before using it as absorbent in order to get zeolite with high adsorption capacity. Previously, the use of pelletized zeolite activated by NaOH-physic and KOH-physic with varied normalities was only performed in a diesel engine to observe the engine performance.In this study there were two kinds of activation, that is chemical activation with NaOH activator variation on the normality of 0.25 N, 0.5 N, 0.75 N, and 1.0 N and physical activation with using a temperature of 220 °C for 2 hours. All are made in the form of adhesive zeolite pellets with a diameter of 10 mm and a thickness of 3 mm. From the test results and analysis showed that the use of chemically activated zeolite can improve the performance of 4-stroke petrol engine when compared without using zeolite. The best performance in this experiment obtained at the normality of 0,75 N. At road test, the pelletized zeolite can reduce the fuel consumption 23, 15 %, and 16,51 % at stationary test, and increase acceleration by 14,77 %.Keywords: zeolite adsorbent, variation of normality, activator of NaOH